Menggali Kompetensi Sosial Guru: Tantangan dan Strategi dalam Konteks Pendidikan Abad 21 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore the importance of teachers’ social competence in dealing with the challenges of social interaction in multicultural school environments in the 21st century. Social competence is a fundamental aspect in fostering harmonious relationships between teachers, students, parents, and other school stakeholders. The research was conducted through literature reviews and interviews with three teachers from different schools in Riau Province, Indonesia. The findings reveal that teachers face various challenges such as diverse student characters, lack of socio-emotional training, and excessive administrative workload. Strategies employed include the use of digital communication, empathy, collaboration, and continuous self-development. This study recommends the importance of social competence training for teachers and the need for institutional policies to support the holistic development of teacher professionalism.